Pemberdayaan Kelompok Ibu-ibu dan Remaja Puteri dalam Pelestarian Masakan Khas Palembang (Tekwan) - Emilia Susanti; Afrizal; Nurdiana; Roswati; Rizki Fiprinita (Tasnim Journal for Community Service, 2022)
Indonesian traditional cuisine is one of the nation's wealth that must be preserved. Considering of foreign cuisine development which is more compatible with the tastes of the Indonesian people, especially the current millennial generation. The purpose of this activity were to give training to the community in preserving the Indonesian traditional cuisine and to give the knowledge to the community of the importance of preserving traditional cuisine, especially tekwan, in increasing communities income. The methods used in this activity were the lecturing and practicing method. As a result, the participants looked like enthusiastic in participating in each step of the activity and hoped that activities could continue to increase knowledge and family income.